2013
DOI: 10.1108/md-11-2012-0792
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial and innovative competences, are they the same?

Abstract: PurposeThis paper aims to study competencies between two groups of professionals: employees in innovative companies and entrepreneurs. Therefore the following questions arise: Are these two types of competences the same? Do innovative companies demand an entrepreneurial profile? Are entrepreneurs' companies spontaneously innovative?Design/methodology/approachThis paper analyses personal competences in two different groups of professionals. On one hand the authors work the common characteristics among successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 35 publications
0
33
0
5
Order By: Relevance
“…Jena & Sahoo, 2014;Mitchelmore & Rowley, 2010, 2013Taatila, 2010) after testing in educational settings. While studies have recognised the connection between entrepreneurship and innovation (Becherer & Maurer, 1999;Bergh et al, 2011;Bunk, 1994;Szerb, 2003), we found that innovation and entrepreneurship were also linked (Bjornali & Støren, 2012;Cerinšek & Dolinšek, 2009;Chell & Athayde, 2011;Edwards-Schachter et al, 2015;Gundry, Ofstein, & Kickul, 2014;Kasule et al, 2015;Santandreu-Mascarell et al, 2013;Waychal et al, 2011). The fifth area for further research is the different competences in each phase of the innovation process (Standing et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Jena & Sahoo, 2014;Mitchelmore & Rowley, 2010, 2013Taatila, 2010) after testing in educational settings. While studies have recognised the connection between entrepreneurship and innovation (Becherer & Maurer, 1999;Bergh et al, 2011;Bunk, 1994;Szerb, 2003), we found that innovation and entrepreneurship were also linked (Bjornali & Støren, 2012;Cerinšek & Dolinšek, 2009;Chell & Athayde, 2011;Edwards-Schachter et al, 2015;Gundry, Ofstein, & Kickul, 2014;Kasule et al, 2015;Santandreu-Mascarell et al, 2013;Waychal et al, 2011). The fifth area for further research is the different competences in each phase of the innovation process (Standing et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…Self-esteem affects performance, behaviour and attitudes at work because it influences self-perceptions of confidence, worthiness, competence and capabilities. Santandreu-Mascarell et al (2013) emphasise the importance of independence and self-confidence, which both indicate the ambition for autonomy from rules or control by others. According to Cerinšek and Dolinšek (2009), the development of innovation is associated with significant risk and uncertainty.…”
Section: Communication Skillsmentioning
confidence: 99%
“…This has been approached through two broad themes, with the first focusing on personality trait profiling of the entrepreneur and known as the trait approach (E Chell 1986;Entrialgo et al 2001;Andreas Rauch andFrese 2007a, 2007b), while the other is focused on the competencies of the individual entrepreneur and known as the competency approach (Elizabeth Chell 2013;Santandreu-Mascarell et al 2013;Tan and Tan 2012;Thongpoon et al 2012). These two approaches are discussed further below.…”
Section: The Link Between Entrepreneurial Competencies and Business Smentioning
confidence: 99%
“…This has been approached through two broad themes. The first is the trait approach, which focuses on personality trait profiling of the entrepreneur (Entrialgo et al 2001;Rauch and Frese 2007), and the second is the competency approach, which is focused on the competencies of the individual entrepreneur (Chell 2013;Santandreu-Mascarell, Garzon & Knorr 2013;Tan & Tan 2012;Thongpoon, Ahmad & Yahya 2012). The focus of this paper is the competency approach and it is discussed further below.…”
Section: Literature Reviewmentioning
confidence: 99%